1996
DOI: 10.1016/s1010-7940(96)80264-8
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised controlled trial of postoperative autotransfusion with and without a heparin-bonded circuit

Abstract: Autotransfusion has been included in the routine protocol in some units as an effort towards blood conservation. In this study we aimed to measure the efficacy and limitations of autotransfusion and whether a heparin-bonded circuit had any advantage. One hundred five patients were randomised to one of three post-operative treatments. Group 1 (n = 34) was not autotransfused whereas groups 2 (n = 36) and 3 (n = 35) received autotransfusion with the circuit of group 3 coated with heparin. Homologous blood and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Many flow cytometric studies in CPB demonstrate reduction of surface GpIb (van Oeveren et al , 1990), whole‐platelet GpIb by radioassay being preserved (Orchard et al , 1993). Ristocetin‐induced platelet aggregation (RIPA; GpIb‐dependent) decreases during CPB (Lu et al , 1991); both RIPA and surface GpIb have been found to correlate with blood loss (Unsworth‐White et al , 1996). Aprotinin, which reduces post‐bypass bleeding (Laupacis et al , 1997; see below), seems to preserve surface GpIb when used during CPB (Van Oeveren et al , 1990), and permit the return of GpIb when used at the end (Kallis et al , 1994a).…”
Section: Cpb: the First 15 Minmentioning
confidence: 99%
See 4 more Smart Citations
“…Many flow cytometric studies in CPB demonstrate reduction of surface GpIb (van Oeveren et al , 1990), whole‐platelet GpIb by radioassay being preserved (Orchard et al , 1993). Ristocetin‐induced platelet aggregation (RIPA; GpIb‐dependent) decreases during CPB (Lu et al , 1991); both RIPA and surface GpIb have been found to correlate with blood loss (Unsworth‐White et al , 1996). Aprotinin, which reduces post‐bypass bleeding (Laupacis et al , 1997; see below), seems to preserve surface GpIb when used during CPB (Van Oeveren et al , 1990), and permit the return of GpIb when used at the end (Kallis et al , 1994a).…”
Section: Cpb: the First 15 Minmentioning
confidence: 99%
“…van Oeveren et al , 1990) were due to using centrifuged and gel‐filtered platelets, compared to minimally disturbed whole blood, for flow cytometry. However, ~35% loss of surface GpIb has been found in subsequent studies using whole blood and FITC‐conjugated monoclonal antibodies (McAbs) (Kallis et al , 1994a; Mazer et al , 1995; Unsworth‐White et al , 1996; Maquelin et al , 1998). Differences in sampling, case‐mix, CPB techniques, or the use of biotinylated versus FITC‐conjugated McAbs may account for this; in CPB the scope for such variation between studies is vast (Royston, 1992).…”
Section: Cpb: the First 15 Minmentioning
confidence: 99%
See 3 more Smart Citations